Mainstream Values and Subcultural Norms: Masculinity, Heteronormativity and Family Reputation in Oppositional Football Fans’ Communication - Stylianou, Stelios (My University, 2019)
This study is part of a project on antagonistic football fans' communication in Cyprus. Using data from fans' websites game observations and in-depth interviews the project confirms that football fandom is publicly communicated in a binary oppositional manner: on the positive side by praising the superiority of one's own team and fans and on the negative side by exposing the inferiority of rival teams and fans. The corresponding chants slogans posts and other practices are structured around a number of substantive themes (e.g. locality ethnicity nationalism) including gender and sexuality which is predominantly articulated in three subthemes: masculinity heteronormativity and the reputation of one's (typically female) family members. Respective outgroup characterizations i.e. alleged deficits in masculinity heterosexuality and family reputation are typically articulated in extreme and vulgar ways deeming such practices deviant in support of claims that these fan groups constitute a deviant subculture. The ethnographic data presented in this study support this subcultural hypothesis as far as the communicative norms are concerned (fans replace mainstream norms). Still when it comes to underlying values analysis I argue that masculinity heteronormativity and family reputation as elements of the mainstream culture are inconsistent with the subcultural hypothesis (fans reaffirm mainstream values).
Keywords: Antagonistic football fans' communication; Chants slogans posts